KEDUDUKAN PEREMPUAN DALAM MASYARAKAT JEPANG - Indun Roosiani (Universitas Pakuan, 2016)
AbstractIndun RoosianiEntering the Meiji era, which marks the end of the feudal era has greatly changed the lives of Japanese society. The existence of the closing period of the country (political sakoku) which lasted for approximately 250 years, causing various government policies can not necessarily change just like the life of the common. The policies adopted by Meiji's new government cover various fields, such as in family life, law and employment. Similarly, the position and role of Japanese women, has undergone many changes when compared with the previous period.The life and attitudes of Japanese women have undergone tremendous changes in the last 15 years or so of the younger generation. Japanese women can enjoy unprecedented freedom with diver. However, the relationship between men and women has not changed much, as illustrated by some experts as dansei joui, josei yuui (superior male, dominant female).Every country always has a difference in positioning women in social life, as well as Japan. Japan as a country known to be very homogeneous also has a different view, especially before and after the Meiji era. The changes occurring as a result of the Meiji Restoration are not very significant for most Japanese women, because the paradigm that has been rooted for more than 2 centuries is not easy to change the condition of Japanese women.Keywords: women, traditional, Meiji Age, beliefs